Educating for Tolerance: Multicultural Approaches in Islamic Religious Education - Lestari, Putri Ayu (Yayasan Sinergi Kawula Muda, 2024)
This narrative review explores the integration of multicultural values within Islamic education in public schools, focusing on how inclusive practices contribute to tolerance and social harmony. The study aims to analyze existing literature on the topic and evaluate the effectiveness of pedagogical and institutional strategies. A systematic search was conducted across Scopus, Web of Science, ERIC, and Google Scholar using relevant keywords such as